Green Politics in China Environmental Governance and State-Society Relations - Zhang, Joy Y (Pluto Press, 2013)
Based on interviews with members of grassroots organisations, media and government institutions, Green Politics in China is an in-depth account of the novel ways Chinese society is responding to its environmental crisis, using examples rarely captured in Western media or academia. The struggle for clean air, low-carbon conspiracy theories, is transforming Chinese society, producing new forms of public fund raising and the encouraging the international tactics of grassroots NGOs. In doing so, they challenge static understandings of state-society relations in China, providing a crucial insight into the way in which China is changing internally and emerging as a powerful player in global environmental politics.